3 Dimensional Finite Element Simulation of Seam Welding Process - Saleem, J.; Majid, A.; Bertilsson, K.; Carlberg, T. (Elektronika ir Elektrotechnika, 2013)
The versatility, rich mathematical formulations and robustness of finite element methods make them attractive for simulations for a wide range of problems. Two dimensional models concerning the seam welding process do have some limitations. The longitudinal two dimensional models cannot be used to examine the effects of the electrode shape and thickness regarding heat generation during the seam welding process. The transversal two dimensional models are not helpful for examining the nugget growth during the seam welding process. The heat energy generated during the seam welding process mainly depends on the resistance between the electrodes, welding current, rotational speed and the geometry of the electrodes. The settings for appropriate parameters in relation to a seam welding machine, with regards to sheets of different thicknesses, depends on trial and error methods. These methods are expensive and time consuming. The three dimensional model developed in this paper is a step towards selecting the appropriate welding parameters so as to produce a good welding nugget. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5398